Glaciological Data Collected by the 48th–54th Japanese Antarctic Research Expeditions during 2007–2013 - MOTOYAMA, Hideaki; FURUKAWA, Teruo; FUJITA, Shuji; SHINBORI, Kunio; TANAKA, Yoichi; LI, Yuansheng; CHUNG, Ji-woong; NAKAZAWA, Fumio; FUKUI, Kotaro; ENOMOTO, Hiroyuki; SUGIYAMA, Shin; ASANO, Hitoshi; et al. (2015)
P(論文) departmental bulletin paper